2021
DOI: 10.32615/ps.2021.019
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and photosystem characteristics of wild-type and Chl b-deficient mutant in tree peony (Paeonia suffruticosa)

Abstract: In order to explore the adaptive strategies of tree peony yl1 mutant in response to photooxidative stress, the changes of biochemical parameters, chlorophyll fluorescence, and the modulated 820-nm reflection of yl1 mutant and wildtype plants were compared. We found the activities of superoxide dismutase and catalase, the contents of soluble protein, proline, superoxide radicals, hydrogen peroxide, malondialdehyde, and relative electrical conductivity were significantly higher than those of the wild type. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Relative electrical conductivity and malondialdehyde content: The relative electrical conductivity (REC) was assessed as previously described (Zhang et al 2021). Fresh leaves (0.10 g) were rinsed and cut into thin strips, then mixed with 6 mL of distilled water, and incubated at room temperature for 24 h. The initial electrical conductivity (EC1) was measured with an electrical conductivity meter (DDS-11A, Shanghai, China).…”
Section: Soluble Protein Soluble Sugar and Proline Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…Relative electrical conductivity and malondialdehyde content: The relative electrical conductivity (REC) was assessed as previously described (Zhang et al 2021). Fresh leaves (0.10 g) were rinsed and cut into thin strips, then mixed with 6 mL of distilled water, and incubated at room temperature for 24 h. The initial electrical conductivity (EC1) was measured with an electrical conductivity meter (DDS-11A, Shanghai, China).…”
Section: Soluble Protein Soluble Sugar and Proline Contentmentioning
confidence: 99%
“…O2 •content was measured by the method of Zhang et al (2021). Fresh leaf samples (1.0 g) were homogenized in 5 mL of PBS (65 mM, pH 7.8), filtered, and centrifuged for 10 min at 10,000 rpm.…”
Section: Soluble Protein Soluble Sugar and Proline Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…REC was measured using an electrical conductivity meter (DDB-303A, INESA, China), following (Zhang L. X. et al, 2021) with a slight modification. Leaf samples were washed with distilled water and then placed in tubes with 10 ml of distilled water.…”
Section: Relative Electrical Conductivitymentioning
confidence: 99%
“…How serious the plant is affected under certain stress can be accurately reflected by some physiological and biochemical indices. Previous research has shown that plants respond to external stress by enhancing antioxidant enzyme activities, like peroxidase and superoxide dismutase, to remove reactive oxygen species (ROS) from the body and weaken lipid oxidation in the cell membrane [ 10 , 11 ], as well as the synthesizing osmoregulatory substances like proline and soluble protein to maintain the water balance inside and outside the cell [ 12 , 13 ]. Furthermore, the level of malondialdehyde and relative conductivity can be used to characterize the severity of cell damage [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%